Ion insertion into individual 7,7,8,8-tetracyanoquinodimethane nanoparticles. - Zhou, X; Cheng, W; Compton, R (Royal Society of Chemistry, 2015)
We report the quantification of partial ion insertion into individual 7,7,8,8-tetracyanoquinodimethane nanoparticles. It is shown that both potassium and sodium ions can be inserted into single TCNQ nanoparticles from aqueous solution. The extent of both potassium and sodium insertion into individual nanoparticles is quantitatively measured and shown to be partial and sodium ion shows a higher extent of insertion. The insertion process is inferred to be limited and controlled by the formation of a thin shell of salt, Na+/K+ TCNQ·- formed at the surface of the nanoparticle.